Influence of Imposed Optic Flow Characteristics and Intention on Postural Responses - Barela, Ana M. F.; Barela, Jose A. [UNESP]; Rinaldi, Natalia M. [UNESP]; de Toledo, Diana R. [UNESP] (Human Kinetics Publ Inc, 2009)
This study examined the influence of both optic flow characteristics and intention on postural control responses. Two groups of 10 adults each were exposed to the room's movement either at 0.6 cm/s (low velocity group) or 1.0 cm/s (high velocity group). All the participants stood in the upright stance inside of a moving room and were informed about the room movement only after the fourth trial as they were asked to resist to its influence. Results revealed that participants from both groups were influenced by the imposed visual stimulus in the first trials, but the coupling strength was weaker for the high velocity group. The request to resist the visual influences decreased visual influences oil body sway, but only for the low velocity group. These results indicate that intention might play a role in stimulus influences on body sway but it is stimulus dependent.
Keywords: vision; postural control; perception-action; moving room